E-urbanism: E-commerce, migration, and the transformation of Taobao villages in urban China. (August 2019) - Lin, Yanliu
Abstract: The development of information and communications technology (ICT) has promoted the rapid growth of e-commerce, which has gradually changed the city. Networking and migration are also key driving forces for contemporary urban development. Although a growing body of literature has studied e-commerce development, there is a lack of theoretical and empirical research to understand the impact of e-commerce and migration on urbanism. This study is an attempt to fill the gap. It firstly proposes a concept framework of E-urbanism that includes three interwoven layers, namely of ICT infrastructure and production networks, social networks and power relations, and urban form and land use. The framework is then applied to understand the influence of e-commerce and migration on the socio-spatial transformation of Taobao villages in Guangzhou city, China. This article concludes that ICT infrastructure and production networks form the foundation of e-commerce development, while social networks of rural migrants are important sources of social capital in the formation of Taobao villages. The existing physical forms provide opportunities for e-commerce growth, which has in turn reshaped them. E-commerce is fundamentally revolutionizing urbanism, the intertwinement of social and spatial reorganization of the city. Highlights: This article develops a concept framework of E-urbanism that includes three interwoven layers. It explores the influence of e-commerce and migration on the transformation of Taobao villages in China. ICT infrastructure and production networks form the foundation of e-commerce development. Social networks of rural migrants are important sources of social capital in the formation of Taobao villages. E-commerce is fundamentally revolutionizing urbanism, the intertwinement of spatial reorganization of the city.